Detailed record of the BELARE 2019-2020 meteorite recovery expedition on the Nansen Ice Field, East Antarctica - Goderis, Steven; Yesiltas, Mehmet; Pourkhorsandi, Hamed; Shirai, Naoki; Poudelet, M.; Leitl, M.; Yamaguchi, Akira; Debaille, Vinciane; Claeys, Philippe (2021)
info:eu-repo/semantics/published